Detecção de faltas de alta impedância em sistemas de distribuição de energia elétrica - Ferreira, Gabriel de Alvarenga (2019)
[EN] In Brazil, the distribution of electric power is predominantly performed by the use of aerial branches, without isolation. Although cheaper, these systems are more susceptible to the occurrence of faults (short circuits). Among these faults, High Impedance Faults (HIFs) still represent a major challenge regarding their detection, since, among other specific characteristics, the low fault current levels generated by these events do not sensitize the conventional protection schemes of these systems, largely based on overcurrent relays. In this scenario, this work has as main objective a broad study in relation to the detection of HIFs in distribution systems. After a large bibliographic review and the definition of the most relevant methods, according to some criteria of importance, two of these methods are chosen for simulation. Additionally, a new method based on Discrete Wavelet Transform is proposed. After the detailed presentation of the methods and methodology used for the simulations in the PSCAD software, the results and discussions regarding the simulation cases are also presented. Finally, the conclusions and proposals for future works are presented.